UPAYA PENINGKATAN KETERAMPILAN TEKNIK DIGITAL SISWA SMK N 1 PAINAN MELALUI PEMBUATAN MEDIA PEMBELAJARAN GERBANG LOGIKA - Irma Husnaini; Asnil Asnil; Fivia Eliza (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
One of the advantages of Vocational High School (SMK) is that graduates are ready to work. For this reason, students must be equipped with skill abilities in accordance with existing technological developments. In the last few years, the development of digital technology has been very advanced which has caused Vocational High School to be required to prepare their students to adapt to existing developments. SMKN 1 Painan is one of the productive Vocational Schools that develops new study programs namely Audio Video Engineering (TAV), one of the objectives is to prepare students to have the skills to enter employment. The obstacle faced by SMKN 1 Painan is to follow the development of digital technology, especially in terms of facilities, this is because the TAV study program is still new. Through the creation of logic gate learning media, it is expected to help the obstacles faced by SMKN 1 so that the existing problems can be addressed properly